2022
DOI: 10.1177/00034894221078367
|View full text |Cite
|
Sign up to set email alerts
|

Operative Surveillance of Airway Hemangiomas in PHACE Syndrome

Abstract: Objective: PHACE is a rare syndrome that can present with airway hemangiomas. Management for these patients is variable and the utilization of operative endoscopic airway evaluation has not been described. The objectives of this study were to identify the incidence of airway symptoms in patients being evaluated for PHACE syndrome and determine the utility of operative endoscopy. Methods: An IRB-approved retrospective cohort study was conducted on consecutive pediatric patients with head and neck infantile hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Truong et al 22 and Elluru et al 6 proposed using FFL followed by operative endoscopy for confirmation. However, since Eshaq et al 13 confirmed the findings of Lindstrom et al 12 on the efficacy and safety of FFL in evaluating the pediatric lower airway, Ramprasad et al 23 and Chun et al 24 have both published studies suggesting that in-office lower airway evaluation may be an alternative technique to operative endoscopy for evaluating and monitoring patients at high risk for SGH. Ramprasad et al 23 assessed 36 patients with head and neck IH evaluated for PHACE (posterior fossa anomalies, hemangioma, arterial anomalies, cardiac anomalies, and eye anomalies) syndrome and found that there was a low probability of detecting an SGH lesion in the airways of clinically asymptomatic patients with PHACE syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…Truong et al 22 and Elluru et al 6 proposed using FFL followed by operative endoscopy for confirmation. However, since Eshaq et al 13 confirmed the findings of Lindstrom et al 12 on the efficacy and safety of FFL in evaluating the pediatric lower airway, Ramprasad et al 23 and Chun et al 24 have both published studies suggesting that in-office lower airway evaluation may be an alternative technique to operative endoscopy for evaluating and monitoring patients at high risk for SGH. Ramprasad et al 23 assessed 36 patients with head and neck IH evaluated for PHACE (posterior fossa anomalies, hemangioma, arterial anomalies, cardiac anomalies, and eye anomalies) syndrome and found that there was a low probability of detecting an SGH lesion in the airways of clinically asymptomatic patients with PHACE syndrome.…”
Section: Discussionmentioning
confidence: 88%